Uplifting Culture and Local Wisdom in the Conservation System of Micro Small and Medium Enterprises - Soraya, Syazarah; Wulandari, Yuni; Utari, Utari (Pusdikra-Publishing.com, 2024)
Environmental conditions greatly influence the quality of life of humans and other living creatures, so it is necessary to pay attention to strong and consistent environmental protection and management conditions by all stakeholders. Various principles are used in environmental protection and management. One of these principles is culture and local wisdom. Local wisdom is noble values ??that apply in community life to, among other things, protect and manage the environment sustainably. Protection and management of the environment must also pay attention to the noble values ??that apply in the community's life system. One of the government's efforts to improve the community's economy is through strengthening cooperatives and increasing the competency of micro, small and medium enterprises (MSMEs). Therefore, cooperatives as the mainstay of the Indonesian economy should be encouraged to continue to modernize so that they can have a maximum positive impact on people's lives.